2013
DOI: 10.1073/pnas.1222368110
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing genes underlying the quantitative trait loci for root-knot nematode resistance in palaeopolyploid soybean by whole genome resequencing

Abstract: The objective of this study was to use next-generation sequencing technologies to dissect quantitative trait loci (QTL) for southern root-knot nematode (RKN) resistance into individual genes in soybean. Two hundred forty-six recombinant inbred lines (RIL) derived from a cross between Magellan (susceptible) and PI 438489B (resistant) were evaluated for RKN resistance in a greenhouse and sequenced at an average of 0.19× depth. A sequence analysis pipeline was developed to identify and validate single-nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 33 publications
5
113
0
Order By: Relevance
“…irregulare and F. graminearum (Glazebrook, 2005;Kou and Wang, 2010;Kou and Wang, 2012). Prior to cloning genes from resistant genotypes associated with quantitative disease resistance in plants, characterizing the type of resistance, identifying and mapping the loci, and narrowing the locus requires a population that is both advanced in generation and large in size to capture the greatest number of recombination events (St. Clair, 2010;Xu et al, 2013). There have been several advancements in this arena where genes associated with quantitative resistance have been cloned and identified.…”
Section: Discussionmentioning
confidence: 99%
“…irregulare and F. graminearum (Glazebrook, 2005;Kou and Wang, 2010;Kou and Wang, 2012). Prior to cloning genes from resistant genotypes associated with quantitative disease resistance in plants, characterizing the type of resistance, identifying and mapping the loci, and narrowing the locus requires a population that is both advanced in generation and large in size to capture the greatest number of recombination events (St. Clair, 2010;Xu et al, 2013). There have been several advancements in this arena where genes associated with quantitative resistance have been cloned and identified.…”
Section: Discussionmentioning
confidence: 99%
“…Three QTLs underlying RKN resistance in PI438489B, were identified on Chrs. 8, 10, and 13 (Xu et al 2013). Ibrahim et al (2011) identified that silencing of tyrosine phosphatase (TP) and mitochondrial stress-70 protein precursor (MSP) genes can decrease gall formation of RKN.…”
Section: Discussionmentioning
confidence: 99%
“…The 50 Chinese lines represented wild soybean, land races, and elite cultivars allowing the researchers to differentiate between candidate genes associated with soybean domestication and improvement. Xu et al (2013) used genome re-sequencing approaches to generate and validate SNPs that were used for QTL mapping of root-knot nematode resistance. Their approach identified two candidate genes responsible for resistance.…”
Section: Applications For Mirna In Soybean Functional Genomicsmentioning
confidence: 99%